Digitalisasi Pertunjukan Musik dengan Tema “Melodie del Mondo Fantastico” - Dani Nur Saputra (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
The digital era demands changes in the form of performing arts. The form of performances that are usually carried out live on an open stage must be able to switch to the packaging of a video that is displayed through digital platforms such as You Tube. This study aims to describe musical performances with the theme Melodie del Mondo Fantastico as an effort to digitize the performing arts. The research was conducted with a qualitative approach. Data collection techniques were carried out through observation and interviews. Data analysis was carried out through the stages of data reduction, data presentation, and conclusions. The results show that digitalization of musical performances needs to be done so that artists and performers can still work and display them digitally via the internet. Some of the efforts made by students in the music education study program include arranging the theme of Melodie del Mondo Fantastico as an expression that describes the current situation, then determining the ten musical groups that will perform, determining the editor of each music group to process the audio and video, asking each player to record his music playing, combine the video of the players. Next, the main editor combines videos from ten music groups into one video which is uploaded to You Tube. The series of activities carried out is a creative process as an effort to change the performing arts from conventional to digital.